2018
DOI: 10.1590/fst.13317
|View full text |Cite
|
Sign up to set email alerts
|

Primary and secondary modeling of Brochothrix thermosphacta growth under different temperature and ph values

Abstract: Bochothrix thermosphacta is an optional aerobic psychrotrophic related to the meat deterioration and consequently loss of a refrigerated cargo contaminated. Predictive microbiology can be used as a quality assurance tool, since it allows the prediction of microbial response based in pass observations. This work aimed model the growth of B. thermosphacta under variation of pH and temperature. For this purpose, the experimental growth data were fitted to the primary models of Baranyi and Roberts and the modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The model estimated Tmin of -12.20 ℃ in the study differed from the reported result (Tmin = -3.36 ℃) [39] , because of the differences in strains and growth media. Similar results were also reported for B. thermosphacta in which Tmin values for the growth of B. thermosphacta in laboratory media were found to be -9.79 ℃ [40] and -11.70 ℃ for meat broth [8] ,…”
Section: Characterization Of the Growth Kinetics Of B Thermosphacta I...supporting
confidence: 88%
See 1 more Smart Citation
“…The model estimated Tmin of -12.20 ℃ in the study differed from the reported result (Tmin = -3.36 ℃) [39] , because of the differences in strains and growth media. Similar results were also reported for B. thermosphacta in which Tmin values for the growth of B. thermosphacta in laboratory media were found to be -9.79 ℃ [40] and -11.70 ℃ for meat broth [8] ,…”
Section: Characterization Of the Growth Kinetics Of B Thermosphacta I...supporting
confidence: 88%
“…To evaluate the behavior of B. thermosphacta in beef, predictive microbiology can be employed to obtain reliable predictive models, in order to monitor bacterial populations and estimate growth parameters [8] .…”
Section: Introductionmentioning
confidence: 99%
“…thermosphacta on the different meat species pig, cattle and chicken. With regard to the pH value, Goncalves et al [47] showed that maximum growth rate of Br. thermosphacta at a pH of 5.5 was lower than at a pH of 6.0.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, it can also be an important ally in the study of the behavior of probiotic cells, such as lactic bacteria, present in milk and its derivatives. Mathematical modeling of the experimental data aids to obtain important data on the growth dynamics of probiotics under the studied conditions, which contributes to the optimization of the food manufacturing process, as well as to the estimation of their functional viability (Gonçalves et al, 2018;Stavropoulou & Bezirtzoglou, 2019).…”
Section: Viability Of Lactobacillus Acidophilus In Whole Goat Milk Yo...mentioning
confidence: 99%
“…In addition, it is noteworthy that dairy goat products are potential food matrices for delivery of probiotic bacteria (Ranadheera et al, 2019) In recent years, interest has grown in the study of the survival kinetics of true probiotic species, applied to different environmental conditions and food matrices, highlighting the fact that fermentation is one of the main strategies for probiotics to synthesize compounds of interest, the probioactives (Champagne et al, 2018;Ryan et al, 2020). Predictive microbiology is a science that investigate parameters for predicting the behavior of microorganisms in food, which provides a fast and reliable path to knowledge about microbial growth, inactivation, and survival under specific conditions (Gonçalves et al, 2018;Ross & McMeekin, 1994).…”
Section: Introductionmentioning
confidence: 99%